1965
DOI: 10.1063/1.1702966
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Rutile of Controlled Composition from Borate Fluxes

Abstract: Rutile crystals of controlled composition have been grown from Na2O·3B2O3 and K2O·3B2O3 fluxes. The compositions were controlled by the use of various atmospheres of known oxygen activity as the equilibrium vapor phase. The crystals are prisms 2 to 10 mm in length and 0.1 to 0.3 mm in thickness. The morphology of the crystals and their response to changes in temperature, oxygen activity, and flux composition are described. The average dislocation density is 4×104 cm−2, but dislocation-free areas can be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…A general observation was that the PXRD patterns of By analogy with the study by Berkes et al (1) the phase obtained at the lower fugacity limit of the rutile phase field rutile phases prepared in the presence of borate flux showed severe preferred orientation, with strong enhanceshould contain the maximum boron content. Accordingly these products at each temperature were subjected to de-ment of the intensities of the {hh0} r reflections.…”
Section: Rutile Composition Pxrd and Em Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…A general observation was that the PXRD patterns of By analogy with the study by Berkes et al (1) the phase obtained at the lower fugacity limit of the rutile phase field rutile phases prepared in the presence of borate flux showed severe preferred orientation, with strong enhanceshould contain the maximum boron content. Accordingly these products at each temperature were subjected to de-ment of the intensities of the {hh0} r reflections.…”
Section: Rutile Composition Pxrd and Em Studiesmentioning
confidence: 87%
“…The thermal parameters are larger for the boron doped rutile and the R factors are considerably higher. A difference Fourier map showed that the main residual electron density occurred at (1/2 0 0) and related positions, Berkes et al (1) suggested that boron could be located at tetrahedral sites in the rutile structure. However, charge balance calculations suggest that this is not very likely.…”
Section: Rutile Composition Pxrd and Em Studiesmentioning
confidence: 97%
“…Contra ry to a prediction that the presence of the glassy phase would stimulate rod formation, the TiO 2 rods were not obtained with the Na 2 OE2.10B 2 O 3 powder. Solubility of titanium oxide was moderate at 700 C:`13 mol÷ in Na 2 OE2B 2 O 3 13) and`3 mol÷ in Na 2 OE3B 2 O 3 , 11) and the formation of rutile rods in the case of Na 2 OE2B 2 O 3 powder under the same heating treat ment has been observed. Thus, the Ti(IV) solubility in the Na 2 OE2.10B 2 O 3 matrix must be high enough to precipitate titanium oxide when similarity in composition between the two matrices is taken into consideration.…”
Section: Discussionmentioning
confidence: 82%
“…Since borates are good flux for titanium oxide, a properly con trolled process of heatingcooling Ti(IV) containing flux may precipitate titanium oxide or its derivative crystals. Indeed, Berkes et al 11) grew rutile crystals out of sodium hexaborate, Na 2 OE3B 2 O 3 as they gave a TiO 2 solubility curve for the pseu dobinary system TiO 2 Na 2 OE3B 2 O 3 , where the liquidus lies at 700 C for 3÷ (mole)TiO 2 containing solution. In our previ ous study, even crystalline potassium metaborate in contact with a titanium oxide layer on titanium substrates yielded nanosize potassium hexatitanate at 700 C, well below the melting temperature (T m 950 C) of the borate.…”
Section: Introductionmentioning
confidence: 99%
“…13) Since borates are good solvents for TiO 2 , K 2 Ti 6 O 13 will be precipitated from a TiO 2 containing potassium borate flux, though Berkes et al 14) grew rutile using a sodium borate as the flux. In this case, solubility curves of TiO 2 in the flux or phase diagrams for the relevant systems are important.…”
Section: Introductionmentioning
confidence: 99%